Arabic Symbols on Rajah with the Perspective of Mantiq Science and Al-Azhar Interpretation - Siregar, Sri Dewi Priwarti; Abdurrahman, Maman; Syihabuddin, Syihabuddin (Aphorisme: Journal of Arabic Language, Literature, and Education, 2022)
This page explains the use of Mantiq in perspective to analyze rajah which is familiar in Indonesia, the science of mantiq which is often used to study a problem in depth. The qualitative-library research method was used in this study. The problem of library research involves studying rajah studies in various books and previous research. Through analysis of studies and interviews with various users of the rajah, data were collected in the form of rajahs and symbols containing Arabic writing and letters. After collecting data, the writer reduces and presents the data in the form of an analysis. Because this study’s objects are diagrams in the form of symbols and text, the authors use Charles S. Peirce's semiotic analysis paradigm in analyzing the data. After tracing, it was discovered that certain rajah contained symbols of Arabic letters and fragments of verses from the Al-Qur’an. The findings of this study are compared with Buya Hamka's interpretation of Al-Azhar verses 190-197, which states that the use of a rajah is not justified even though it contains many Arabic symbols.